Joustavaa lauseoppia - Alho, Irja (Virittäjä, 1997)
Towards flexible syntax (englanti) 4/1997 (101) Irja Alho (University of Joensuu; fi) TOWARDS FLEXIBLE SYNTAX The article examines the relationship between traditional syntax, the study of syntax and the teaching of syntax. The flexible nature of both language itself and the selection of conceptual tools available to analyse its structure is highlighted. The syntax of a language may contain rather more variation than indicated by traditional grammars, as is the case with Finnish, for example. It is well known that standard spoken Finnish, even when used somewhat formally, differs in many respects from the well-regulated written language. The structural properties of the spoken language, for instance, can be studied and compared with those of the written language. Concerning syntactic methods, it is argued that the traditional way of analysing sentences by classifying individual words is misleading. The same properties that make it attractive also make it unrealistic. The problem lies in the assumption of a complete and exhaustive system, that every sentence has a single correct analysis in terms of lexical classes and the form and function of each word. The traditional view that each word in a sentence is a functional constituent of the whole sentence is critically examined in the article. The writer points out that the 1915 committee on Finnish grammar chaired by E. N. Setl in fact strongly recommended the phrasal analysis of sentences. According to this approach, the parts or members of a sentence that can be identified immediately may, and in most cases do, include more than just one word. The writer, however, acknowledges that it is not easy to argue in favour of just one phrasal analysis of a sentence. Judgements over where the phrasal breaks are located can vary. This is the key point of the article. If the syntax of a language is based on phrasal analysis, then flexible analyses of sentences must be accepted. Other structural views should be utilized, such as analysis based on the crucial role of the verb in conveying information concerning the other constituents of the sentence.